Postembryonic development of rectal pads in bees (Hymenoptera, Apidae) - Santos, Carolina Gonçalves; Neves, Clóvis Andrade; José, Cola Zanuncio; Serrão, José Eduardo (The Anatomical Record, 2009)
The morphology and development of the digestive tract of insects has been extensively studied, but little attention has been given to the development of the rectal pads. These organs are responsible for absorption of water and salts. In insects where they occur, there are usually six ovoid rectal pads located in the medial-anterior portion of the rectum. The rectal pad has three types of cells: principal, basal, and junctional. The arrangement of these three cell types delimits an intrapapillary lumen. The aim of the current study is to describe the development of the rectal pads during postembryonic development of Melipona quadrifasciata anthidioides and Melipona scutellaris. Specimens were analyzed at the following developmental stages: white-, pink-, brown-, and black-eyed pupae, and adult workers. The development of the rectal pad begins as a thickening of the epithelium in white-eyed pupae at 54 hr. At this stage, there is neither a basal cell layer nor intrapapillary lumen. The basal layers begin to form in the pink-eyed pupa and are completely formed at the end of the development of the brown-eyed pupa. In the brown-eyed pupal stage, the intrapapillary lumen is formed and the junctional cells are positioned and completely differentiated. Necrotic and apoptotic cell death were detected along with cell proliferation in the whole rectum during pupal development, suggesting that the development of the rectal pads involves cell proliferation, death, and differentiation. The rectal pads originate only from the ectoderm. Anat Rec, 2009. © 2009 Wiley-Liss, Inc.
Keywords: Development; Digestive tract; Insects; Stingless bees